2005
DOI: 10.1161/01.hyp.0000182662.82666.37
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intake and Risk of Incident Hypertension

Abstract: Abstract-Emerging evidence suggests an inverse relation between vitamin D and blood pressure. We examined the independent association between intake of vitamin D and the risk of incident hypertension among participants of 3 large and independent prospective cohorts: Nurses Health Study I (NHS I; nϭ77 436), NHS II (nϭ93 803), and Health Professionals' Follow-up Study (HPFS; nϭ38 074). Relative risks and 95% confidence intervals for incident hypertension were computed according to quintiles of vitamin D intake u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(37 citation statements)
references
References 31 publications
(37 reference statements)
3
33
1
Order By: Relevance
“…[52][53][54] It is slightly more clear whether supplementation of Vit D decreases arterial pressure. 55,56 In our study, SBP and DBP levels were higher in individuals with MS than without MS. Moreover both systolic and diastolic blood pressure levels reduced as Vit D levels increased.…”
Section: Resultssupporting
confidence: 45%
“…[52][53][54] It is slightly more clear whether supplementation of Vit D decreases arterial pressure. 55,56 In our study, SBP and DBP levels were higher in individuals with MS than without MS. Moreover both systolic and diastolic blood pressure levels reduced as Vit D levels increased.…”
Section: Resultssupporting
confidence: 45%
“…Epidemiological studies have demonstrated the independent association between vitamin D deficiency and CVD risk factors, such as hypertension [2], diabetes mellitus [3], obesity [4], metabolic syndrome [5], subclinical atherosclerosis (intima-media thickness [IMT]) [6], and coronary calcification [7,8]. Hypovitaminosis D has also been associated with cardiovascular events, such as MI [9], congestive heart failure, sudden cardiac death [10] and total mortality [11].…”
Section: Beata Goleniewska Et Al Vitamin D and Coronary Angiogram Imentioning
confidence: 99%
“…10 mg/d. Results from three large prospective studies, Nurses' Health Study I (n 77 436), Nurses' Health Study II (n 93, 803) and the Health Professionals Follow-up Study (n 38 074), found no evidence that a higher intake of vitamin D reduced (or increased) the risk of incident hypertension after multiple adjustments and approaches to the analysis (129) . Diagnosis of hypertension in this study was self-reported, and although self-reported hypertension in a health professionals' study is reasonably reliable, it does cast doubt over the study outcomes.…”
Section: Elevated Blood Pressurementioning
confidence: 99%